(untitled) (International Journal of Food and Nutritional Sciences, 2021)
In order to make infrastructure safer and last longer, researchers are developing a method to monitor the health of civil constructions using Wireless Sensor Networks (WSNs). This system is able to continually monitor factors including strain, vibration, temperature, and displacement via the deployment of a network of wireless sensors. The ability to gather and analyse data in real-time allows for the early identification of structural problems, which in turn allows for more prompt maintenance and the avoidance of catastrophic breakdowns. Easy installation, scalability, and low cost are three benefits of using WSNs. This technology is a huge step forward in civil engineering; it will help with proactive infrastructure management and make sure everyone is safe. Distributed sensor processing is an integral part of WSN, allowing a single control station to monitor the status of several systems across multiple clusters of sensors. The central processing unit (CPU) of a wireless smart sensor is responsible for performing calculations at the node level and imparting the sensor’s intelligence; industrial components may be integrated into smart wireless sensor nodes to enable real-time on-site acquisition of metrics like strain and vibration.